Urinary Bladder Squamous Cell Carcinoma In-Situ in a Background of Condyloma Acuminatum – A Diagnostic Challenge. (9th November 2022) - Pandiri, M; Bharadwaj, H; Cole, L
Abstract: Introduction/Objective: Condyloma acuminatum is a rare lesion of the urinary bladder and urethra, usually associated with extensive anogenital condyloma acuminatum and immunosuppression. It is considered a risk factor for developing urinary bladder squamous cell carcinoma. Methods/Case Report: We report a case of an 80-year-old male with a history of invasive squamous cell carcinoma of the anus, status-post chemoradiation ten years prior, and renal transplantation for end-stage renal disease 15 years prior. He presented with a lesion adjacent to the neoureteral orifice at the bladder dome. Biopsy revealed nonkeratinizing, hyperplastic papillary fronds of squamous epithelium with koilocytic change and viral atypia. The tumor was positive for p16, GATA3, and p40 and negative for high-risk and low-risk Human Papilloma Virus by in-situ hybridization. However, the morphology was consistent with squamous cell carcinoma in-situ arising in a background of condyloma acuminatum, which was concurred by an outside expert. Bladder condyloma acuminata are often challenging to recognize, given their extreme rarity and the possibility of negative low-risk and high-risk Human Papilloma Virus tests. Lack of prior history of anogenital condylomas can further obscure this diagnosis. Results (if a Case Study enter NA): NA. Conclusion: This case raises awareness of condyloma acuminatum as a rare entity that needs to be considered in the differential diagnosis of bladder tumors, especially in immunosuppressed patients. Given that the treatment strategies for squamous cell carcinoma arising from condyloma acuminatum differ from that for urothelial carcinoma with squamous differentiation, distinguishing these lesions from one another is imperative.